PENGARUH MODEL PEMBEAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMAHAMAN SISWA PADA MATA PELAJARAN MATEMATIKA MATERI INTEGRAL KELAS XI SMA NEGERI WOLWAL TAHUN PELAJARAN 2024/2025 - Nursanti Malik; Muthiah Prasong; Ratna A.P. Balikh (STKIP Muhammadiyah Kalabahi, 2026)
His study aims to determine the effect of the Problem-Based Learning (PBL) model on students' mathematical comprehension, specifically on Integral, in grade XI students at Wolwal State Senior High School in the 2024/2025 academic year. The approach used was a quantitative approach with a quasi-experimental research design. The population in this study was all grade XI students, with two classes selected purposively: an experimental class (using the PBL model) and a control class (using a conventional learning model). The instrument used was a mathematical concept comprehension test, the validity and reliability of which have been tested. The results of the data analysis indicate a significant difference between the mathematical comprehension of students taught using the PBL model compared to students taught using the conventional method. Therefore, it can be concluded that the Problem-Based Learning model has a positive effect on improving students' mathematical comprehension of Integral..